Design of an Anti-Corona Device for HVAC Substation Connectors - Ane Miren Larrea; Manuel De La Hoz; Agurtzane Etxegarai; Angel Javier Mazon; Itxaso Aranzabal (Energies, 2022)
One of the aspects to consider during high-voltage (HV) equipment design is the reduction in the probability of corona effect onset. Indeed, the corona effect is related to high electric field values beyond the equipment’s insulation levels and insulation strength, among other factors. This issue can be addressed during the design step, either by modifying the geometry of the electrical device or by including additional elements in the equipment structure to smooth out the voltage gradient along critical regions, such as anti-corona devices. The study of anti-corona devices for HV insulators is well documented, in contrast to substation connectors. Therefore, the present study proposed the design of a novel anti-corona device for HV substation connectors, including a method for the selection of its dimensions. This study shows that the relationship between the dimensional design variables and the critical electrical field on the connector is described by linear and rational functions. Thus, the design process times are cut down due to a reduction in the number of simulations required to run the assessment of the anti-corona device arrangement impact.